2009
DOI: 10.1007/s10562-009-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 Crystallite Size on the Activity of CO Oxidation

Abstract: Nanocrystalline TiO 2 with average crystallite sizes 7 and 15 nm were synthesized by the solvothermal method using titanium n-butoxide and 1,4-butanediol as titanium precursor and solvent, respectively. Four transition metals (Ag, Co, Ni, Pt) were supported on the TiO 2 supports by incipient wetness impregnation with metal loadings 1 and 25 atomic%. For any metal type, metal dispersion and CO oxidation activities were higher when the catalysts were prepared on the larger crystallite size TiO 2 for both high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The samples were measured in a controlled humidity room. The amount of metal active sites for Ag/TiO 2 catalysts was determined using N 2 O pulse chemisorption according to the method described previously by our group [22]. Approximately 100 mg of the catalyst sample was reduced in hydrogen flow (50 cm 3 /min) at 200 8C.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The samples were measured in a controlled humidity room. The amount of metal active sites for Ag/TiO 2 catalysts was determined using N 2 O pulse chemisorption according to the method described previously by our group [22]. Approximately 100 mg of the catalyst sample was reduced in hydrogen flow (50 cm 3 /min) at 200 8C.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…However, they are often inter-related depending on choice of the support [1]. Comsup et al found that stronger Ag-TiO 2 interactions improved the catalytic activity for CO oxidation [14]. Doping of P and Si into TiO 2 resulted in different activities [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The support can disperse the metal particles and induce interactions between Ag and the support [25]. At present, supports for Ag catalysts are divided into two main categories: (1) inert supports such as silica materials [25][26][27]42,52,53,55,56,59] and Al2O3 [60]; and (2) active supports such as CeO2 [32], FeOx [45][46][47], CoOx [48], TiO2 [61][62][63][64], and MnOx [29,58,[65][66][67][68][69]. The CO oxidation activities of Ag catalysts supported on different supports are listed in Table 1.…”
Section: Effect Of Supportmentioning
confidence: 99%
“…The highest catalytic activity for CO oxidation was found on the Ag/Al2O3 catalyst, and the catalytic activity for CO oxidation was strongly related to the reduction activity of the catalyst. Comsup et al [62] found that stronger Ag-TiO2 interactions improved the catalytic activity for CO oxidation. Doping of P and Si into TiO2 resulted in different activities [63,64].…”
Section: Effect Of Supportmentioning
confidence: 99%
See 1 more Smart Citation